'Reframing Healthcare Services through the Lens of Co-Production' (RheLaunCh): a study protocol for a mixed methods evaluation of mechanisms by which healthcare and social services impact the health and well-being of patients with COPD and CHF in the USA and The Netherlands. Issue 9 (7th September 2017) - Hesselink, Gijs; Johnson, Julie; Batalden, Paul; Carlson, Michelle; Geense, Wytske; Groenewoud, Stef; Jones, Sylvester; Roy, Brita; Sansone, Christina; Wolf, Judith R L M; Bart, Bradley; Wollersheim, Hub
Abstract : Introduction: The USA lags behind other high-income countries in many health indicators. Outcome differences are associated with differences in the relative spending between healthcare and social services at the national level. The impact of the ratio and delivery of social and healthcare services on the individual patient's health is however unknown. ' Reframing Healthcare Services through the Lens of Co-Production ' (RheLaunCh) will be a cross-Atlantic comparative study of the mechanisms by which healthcare and social service delivery may impact patient health with chronic conditions. Insight into these mechanisms is needed to better and cost-effectively organise healthcare and social services. Methods: We designed a mixed methods study to compare the socioeconomic background, needs of and service delivery to patients with congestive heart failure and chronic obstructive pulmonary disease in the USA and the Netherlands. We will conduct: (1) a literature scan to compare national and regional healthcare and social service systems; (2) a retrospective database study to compare patient's socioeconomic and clinical characteristics and the service use and spending at the national, regional and hospital level; (3) a survey to compare patient perceived quality of life, receipt and experience of service delivery and ability of these services to meet patient needs; and (4) multiple case studies to understand what patients need to better govern their quality of life and how needs are met by services. Ethics and dissemination: Ethics approval was granted by the ethics committee of the Radboud University Medical Center (2016–2423) in the Netherlands and by the Human Subjects Research Committee of the Hennepin Health Care System, Inc. (HSR #16–4230) in the USA. Multiple approaches will be used for dissemination of results, including (inter)national research presentations and peer-reviewed publications. A website will be established to support the development of a community of practice.